RvE1 Attenuates Polymicrobial Sepsis-Induced Cardiac Dysfunction and Enhances Bacterial Clearance - Chen, Jianmin; Purvis, Gareth S. D.; Collotta, Debora; Al Zoubi, Sura; Sugimoto, Michelle A.; Cacace, Antonino; Martin, Lukas; Colas, Roman A.; Collino, Massimo; Dalli, Jesmond; Thiemermann, Christoph (Frontiers in Immunology, 2020)
The development of cardiac dysfunction caused by microbial infection predicts high mortality in sepsis patients. Specialized pro-resolving mediators (SPMs) mediate resolution of inflammation in many inflammatory diseases, and are differentially expressed in plasma of sepsis patients. Here, we investigated whether the levels of SPMs are altered in the murine septic heart following polymicrobial sepsis-induced cardiac dysfunction. Ten week-old male C57BL/6 mice were subjected to polymicrobial sepsis induced by cecal ligation and puncture (CLP), which is a clinically relevant sepsis model receiving analgesics, antibiotics and fluid resuscitation. CLP caused a significant systolic dysfunction assessed by echocardiography. The hearts were subjected to LC-MS/MS based lipid mediator profiling. Many SPMs were significantly reduced in septic hearts, among which RvE1 had a ~93-fold reduction. Treatment of CLP mice with synthetic RvE1 (1 μg/mouse i.v.) at 1 h after CLP increased peritoneal macrophages number, particularly MHC II- macrophages. RvE1 reduced pro-inflammatory gene expression (interleukin-1β, interleukin-6 and CCL2) in lipopolysaccharide-stimulated bone marrow-derived macrophages (BMDMs) in vitro. RvE1 attenuated cardiac dysfunction in septic mice and increased cardiac phosphorylated Akt; decreased cardiac phosphorylated IκB kinase α/β, nuclear translocation of the NF-κB subunit p65, extracellular signal–regulated kinase 1/2 and c-Jun amino-terminal kinases 1/2. Most notably, RvE1 treatment reduced peritoneal bacterial load and promoted phagocytosis activity of BMDMs. In conclusion, cardiac SPMs, particularly RvE1, are substantially reduced in mice with polymicrobial sepsis. Delayed therapeutic administration of RvE1 to mice with polymicrobial sepsis attenuates the cardiac dysfunction through modulating immuno-inflammatory responses. In addition to the above effects, the ability to enhance bacterial clearance makes RvE1 an ideal therapeutic to reduce the sequalae of polymicrobial sepsis.